Slew Control of Prolate Spinners Using Single Magnetorquer - Juntian, Si; Yang, Gao; Abadi, Chanik (American Institute of Aeronautics and Astronautics, 2016)
E XISTING research [1–5] on the prolate spinning spacecraft attitude maneuver has developed a series of slew algorithms using a single thruster in two categories: half-cone derived algorithms and pulse-train algorithms. Half-cone derived algorithms consist of half-cone (HC), multi-half-cone, dual-half-cone, extended half-cone, sector arc slew, and multisector arc slew, using the precession behavior of a spinning prolate spacecraft. Pulse-train algorithms consist of rhumb line and spin-synch algorithms, which use a train of uniform torque pulses to achieve the attitude maneuver. Pulse-train algorithms can also be used for oblate spacecraft. The existing slew algorithms have been initially developed for specific prolate spacecraft such as penetrators proposed in MoonLITE missions [6]. In the MoonLITE mission, a mothership releases missile-shaped penetrators equipped with thrusters for hard landing on the lunar surface from 100 km altitude. Before impact, a 90 deg spin axis attitude maneuver is required after spinning up the penetrator. The aforementioned slew algorithms can provide low-cost solutions to meet the required 90 deg attitude maneuver and within a small mass budget of the penetrator.